The effect of error correction on ESL student writing / Jean Jihel - Jihel, Jean (2014)
This study investigates the effect of written error correction, and the opinions and preferences regarding written error correction by Form 2 students in Bau, Sarawak. The instruments utilized in this study are questionnaires and students’ writing scripts. A guided descriptive essay entitled: “My Family” was administered for the pre-test. The pre-test writing scripts were checked and graded based on explicit written error correction, also known as “direct” or “over” error corrections (Ferris, 2004). Four treatment sessions for one month duration were carried out before the post-test with the same title was administered again. The writing scores of both the pre-test and post-test were graded based on Chia’s (2010) writing scoring rubrics. The scoring rubrics consist of four writing variables: content, organization and development, readability and grammar and mechanics. A paired sample t-test was performed to compare the students’ performance in their pretest and post-test. The findings of this study reveal that the students performed well after written error correction where the total mean score for pre-test is 5.71 and 8.17 (sig. 0.001) for the post-test. The writing variable which benefits most from written error correction is the fourth variable, grammar and mechanics. The pre-test mean for grammar and mechanics is 5.77 and the post-test mean is 8.82 (sig. 0.001). The three section questionnaire used in this study was adapted from Amrheria (2010) and Grami (2005). The data collected from the questionnaires were analysed descriptively. The findings depicted that the students’ opinions were positive (between “agree” and “strongly agree”) towards written error correction with a total of 90.1 percent (mean: 4.2). As for the students’ preferences regarding written error correction, the majority of respondents “agree” and “strongly agree” with a total average of 92.2 percent (mean: 4.3) who claimed that they prefer written error correction. This study was conducted to fill a gap in the existing literature on investigating the effects of written error correction on ESL student writing among lower secondary school students. The implications of this study include the importance for teachers, researchers, students and ESL teaching field in general. This study is just a “journey of a thousand miles that begins with a single step” (Lao-tzu) and further research in the field of error corrections is greatly needed to improve students’ command of English.